EFFECT OF SPIRITUAL BASED MINDFULNESS INTERVENTION ON EMOTIONAL CONTROL IN ADULT PATIENTS WITH PULMONARY TUBERCULOSIS - Donatus Korbianus Sadipun; Meidiana Dwidiyanti; Megah Andriany (Belitung Nursing Journal, 2018)
Background: Emotions have an impact on the healing process as it affects the body's defense system. The work that can be done to control the emotions of pulmonary TB patients is mindfulness with a spiritual approach. Objective: To examine the effect of spiritual based mindfulness intervention on the emotional control in adult patients with pulmonary TB. Methods: This was a pre-experimental study with one group pre-posttest design with a total of 45 adult patients with pulmonary TB recruited purposively in the public health centers. A questionnaire of emotional regulation was used for data analysis. Paired t-test was used for data analysis. Results: There was a significant difference in emotional control between before and after given spiritual based mindfulness intervention with p = 0.000 (<0.05). Conclusion: The spiritual based mindfulness intervention has a significant effect to improve the emotional control of adult patients with pulmonary TB. This can be used as one of the efforts to control the emotions of pulmonary TB patients as well as to speed the healing process.